Ecommerce as internationalization strategy: an exploratory study based on premium fashion brazilian brands: case study of farfetch - Rosa, Renata Ferreira da (2016)
As stated by Hoffmann and Coste-Manière (2012) 'The web is a mass medium that contrast completely with the traditional codes of exclusivity associated with the luxury industry, and has long been simply rejected by the luxury industry for being an illegitimate distribution channel.' Meanwhile this market presents an incomparable pace of growth and is gradually changing the existing retailing business model and companies must be aware of this change and capable to adapt to it. The internet and cross-border sales already changed the competition throughout retailing and it will increase even more, so companies must be ready to face it. Internet has shown its great opportunity for all markets, although luxury/premium market is not yet taking the proper advantage of its potential, but the necessity to be an omnichannel business strategy is growing. This paper presents an exploratory research based on a case study of how premium fashion Brazilian brands are using Farfetch, e-commerce, as an entry market strategy and how this affects them. The research question of this study is: How is Farfetch helping on the internationalization of Brazilian premium fashion brands?, and in order to answer it was conducted an in-depth interview with the Brazilian head of business development of Farfetch, apart an extensive secondary data research. As expected the study found a list of trade-offs of using an e-commerce, luxury specialized, with a marketplace approach to the brands willing to internationalize. As stated by Altagamma and McKinsey (2015) study '[...] luxury brands have no choice but to embrace the digital era and become truly omnichannel. This will require them a radical rethinking of both their customer experience of their consumer engagement strategy.' Looking either from the Farfetch point of view, trying to understand why they offer this opportunity to the brands, or also from the brand side if this is a manageable approach. This study presents a contribution for both sides, trying to give tools to the brands on understanding the internationalization reasons and approach, as well as explaining Farfetch business model, and the advantages it can bring to them, at the same time of a general market trend analysis for Farfecth.